Single-molecule analyte recognition with ClyA nanopores equipped with internal protein adaptors - Soskine, Misha (J Am Chem Soc, 2015)
Nanopores have been used to detect molecules, to sequence DNA or to investigate chemical reactions at the single-molecule level. Because they approach the absolute limit of sensor miniaturisation, nanopores are amenable to parallelisation and could be used in single-cell measurements. Here we show that single enzymes can be functionally and reversibly trapped inside the confined space of a ClyA nanopore. Remarkably, the binding of ligands to the internalised proteins is mirrored by specific changes to the nanopore conductance. Conveniently, the manipulation of the charge of the protein allowed increasing of the residence time of the protein inside the nanopore. Nanopores with internalised protein adaptors can be used to study proteins in real-time or can be incorporated into inexpensive portable devices for the detection of analytes with high selectivity.